Quality of Life Determinant Factors in Tuberculosis Patients in Indonesia: Literature Review - Liena Sofiana; Sri Achadi Nugraheni (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Tuberculosis patients undergo treatment and care for a long time which will have an impact on their well-being. Good patient welfare will have an impact on the patient's quality of life in their daily lives. The quality of life possessed by tuberculosis patients is important because it can affect the success of treatment. The purpose of this study was to analyze the factors that influence the quality of life of tuberculosis patients in Indonesia. The research design used is a literature review using keywords based on PICo using a database of research articles, namely ScienceDirect, ProQuest, PubMed, Google Scholar and Garuda from 2016-2021. There were 13,782 articles with 18 relevant articles for review and analysis. The low quality of life of tuberculosis patients is influenced by factors of age, education, stress, depression, stigma, medication adherence and social support.  Abstrak: Pasien tuberkulosis menjalani pengobatan dan perawatan yang cukup lama yang akan berdampak pada kesejahteraan yang dialaminya. Kesejahteraan pasien yang baik akan berdampak pada kualitas hidup pasien dalam kesehariannya. Kualitas hidup yang dimiliki oleh pasien tuberkulosis merupakan hal yang penting, karena dapat mempengaruhi kesuksesan pengobatan. Tujuan penelitian ini adalah untuk menganalisis faktor-faktor yang mempengaruhi kualitas hidup pasien tuberkulosis di indonesia. Desain penelitian yang digunakan merupakan literature review dengan menggunakan kata kunci berdasarkan PICo dengan menggunakan data base artikel penelitian yaitu ScienceDirect, ProQuest, PubMed, Google Scholar dan Garuda dari tahun 2016-2021. Didapatkan 13.782 artikel dengan 18 artikel yang relevan untuk dikaji dan dianalisis. Rendahnya kualitas hidup yang dimiliki oleh pasien tuberkulosis dipengaruhi oleh faktor usia, pendidikan, stres, depresi, stigma, kepatuhan pengobatan dan dukungan sosial.